KETERLIBATAN ORANG TUA DALAM PENDIDIKAN SEKS ANAK USIA DINI - Riris Wahyuningsih; Habibah Afiyanti Putri; Bella Arini Haq; Raden Rachmy Diana (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The phenomenon of sexual violence against children in Indonesia, which has increased by 300% in the last decade, demands a preventive approach through early childhood sexuality education, yet still faces strong cultural resistance. This research explores the dynamics of parent-teacher collaboration in implementing early childhood sexuality education at TK Tunas Harapan Banyuwangi, focusing on paradigm transformation, collaborative mechanisms, and their impact on children's protective understanding. Employing qualitative educational ethnography with an interpretive-constructivist paradigm, the study involved 12 parents, 6 teachers, and 1 principal during March-June 2024. Data were collected through participatory observation, semi-structured interviews, focus group discussions, and document analysis, then analyzed using the Miles model with triangulation for validity. Findings reveal paradigm transformation from resistance to acceptance through andragogy-based "parent classes," three-pillar collaborative mechanisms (shared vision building, synchronized capacity building, and communication protocols), and positive impacts including enhanced children's body awareness, changes in family communication patterns, and transformation of teaching practices toward child-centered approaches. This research contributes to developing locally-based collaborative models for sexuality education relevant to Indonesia's sociocultural context.